2020
DOI: 10.1101/2019.12.31.19016212
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Polygenic Risk for Depression is Associated with the Severity and Rate of Change in Depressive Symptoms Across Adolescence

Abstract: Adolescence marks a period where depression will commonly onset and previous research using twin studies has suggested that genetic influences play a role in how depression develops and changes across adolescence. Recent genome-wide association studies have also shown that common genetic variants − which can be combined into a polygenic risk score (PRS) − are also implicated in depression. However, the role of PRS in adolescent depression and changes in adolescent depression is not yet understood. We aimed to … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 68 publications
(102 reference statements)
1
3
0
Order By: Relevance
“…We observed significant positive associations between depression PRS and phenotypic depression. This finding is consistent with previous work linking higher polygenic loading for MDD with elevated depressive symptoms during adolescence in European-ancestry populations (Kwong et al, 2019(Kwong et al, , 2020Rice et al, 2019). Notably, the depression PRS accounted for between 1.5%-2.5% of the variance in past year MDD and MDE, paralleling the amount of variance explained in European samples (1.5%-3.2%) (Howard et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We observed significant positive associations between depression PRS and phenotypic depression. This finding is consistent with previous work linking higher polygenic loading for MDD with elevated depressive symptoms during adolescence in European-ancestry populations (Kwong et al, 2019(Kwong et al, , 2020Rice et al, 2019). Notably, the depression PRS accounted for between 1.5%-2.5% of the variance in past year MDD and MDE, paralleling the amount of variance explained in European samples (1.5%-3.2%) (Howard et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…Extant work has indicated that depression PRS were associated with childhood-persistent depression and early-adult onset depression in a predominantly European-ancestry sample (Kwong et al, 2019). Other work has shown that a depression PRS was associated with increasing and high depressive symptoms across childhood and adolescence (Lussier et al, 2020) and a steep increase in depressive symptoms in adolescence and young adulthood (Kwong et al, 2020) in Europeanancestry samples. Additional research has indicated that in a European-ancestry sample, depression PRS were associated with late adolescent depression, but not low or early-onset adolescent depression (Rice et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…At ages 9 to 12 girls and caregivers were asked about depression symptoms in the past month, and at ages 13 and older were asked about symptoms in the past month and past year. Participants were classified as having had MDD if they met DSM-IV criteria at any study visit by combined parent and child report (n=58; n=31 met criteria at ages 9-14; n=27 met criteria at ages [16][17][18][19][20]. Participants with MDD did not differ from those without MDD on sociodemographic variables (race, pubertal timing or tempo, and financial strain), age, or the number of fMRI scans (Table 1).…”
Section: Assessment Of Depressionmentioning
confidence: 99%
“…The peak incidence for MDD occurs during adolescence [16][17][18] , especially for girls 19 . Adolescence is also a developmental period in which reward-related activation, particularly of the VS, changes and peaks [20][21][22] .…”
Section: Introductionmentioning
confidence: 99%